1999
DOI: 10.1002/(sici)1098-2264(199912)26:4<336::aid-gcc8>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Combined spectral karyotyping and DAPI banding analysis of chromosome abnormalities in myelodysplastic syndrome

Abstract: Spectral karyotyping (SKY) is a new molecular cytogenetic technique that allows simultaneous visualization of each chromosome in a different color. We have used SKY for comprehensive analysis of 20 myelodysplastic syndromes (MDSs) (13 primary MDSs, 3 therapy‐related MDSs, and 4 acute leukemias developed from MDS, including 1 cell line established from a secondary leukemia), previously analyzed by G‐banding. To locate the chromosomal breakpoints, DAPI‐counterstained band images from all metaphases were transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 29 publications
(17 reference statements)
4
33
0
Order By: Relevance
“…[10][11][12][13][14][15] Patient characteristics, karyotypes, results of FISH, and mutation status of TP53 and AML1 of the three cases are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] Patient characteristics, karyotypes, results of FISH, and mutation status of TP53 and AML1 of the three cases are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has been observed in approximately 2% of patients with childhood acute lymphoblastic leukemia (ALL), [6][7][8][9] but to our knowledge only in seven cases of de novo MDS and AML. [10][11][12][13][14][15] In these seven patients the mutational status of TP53 was not examined. In t-MDS and t-AML a similar amplification or duplication of chromosome band 11q23 including the unrearranged MLL gene has been observed in 17% of the patients closely associated with mutations of the TP53 gene.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29] These studies demonstrate that FISH analysis can provide additional information about chromosome 5 abnormalities. It would, therefore, be recommendable to use FISH techniques to study those cases with monosomy 5 and/or marker chromosomes in order to identify translocations with a breakpoint in 5q or possible 5q-chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…16 It has also been shown that the coiled-coil region of ETO could oligomerize with AML1-ETO protein, thus recruiting the nuclear corepressor N-CoR responsible for transcriptional repression of AML1 target genes and resulting in impaired differentiation of primary hematopoietic precursors. 17,18 Recently, we and others have reported other mechanisms of inactivation of AML1 in hematological malignancies, through point mutations of the gene in AML and in MDS [19][20][21][22][23][24][25] or through gene amplification, [26][27][28][29][30][31][32] a rare event mainly observed in acute lymphoblastic leukemia (ALL). In this review, we focused on those two other mechanisms of AML1 deregulation in hematological malignancies.…”
Section: Introductionmentioning
confidence: 99%